Militaryzacja ciała w wierszach Władysława Sebyły - Dębińska, Aleksandra (Zagadnienia Rodzajów Literackich, 2024)
World War I was associated with a vision that encouraged Poles to join the fight to regain independence. Romantic myths invoked in this context led to the idealization of wartime events and the heroization of those who took part in them. For this reason, Polish war literature differs from pacifist descriptions of war in Western European literature, but in the middle of the interwar period, Władysław Sebyła publishes his poetic debut, Pieśni szczurołapa (Songs of rat-catcher), in which he includes a series of Four Poems about War. His aversion to brutal militarism and armed conflict is revealed in those poems, so the main purpose of the article is to show how the poet creates an anti-military and catastrophic war landscape. I point out that the author focuses around the “bodily cycle of the soldier” — from life in the barracks through combat and finally, maiming or death. In my analysis, I will use Adam Dziadek’s project of somatic criticism to see the relationship between the body and rhythm and words in Sebyła’s poetry.